2015
DOI: 10.1186/s12866-015-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of endosymbiotic bacteria infecting cassava whiteflies in Africa

Abstract: BackgroundCassava provides over half of the dietary requirement for more than 200 million poor in Africa. In recent years, cassava has been affected by an epidemic of a virus disease called cassava brown streak disease (CBSD) that is spreading in much of eastern and central Africa, affecting food security and the economic development of the poor. The viruses that cause CBSD are transmitted by the insect vector whitefly (Bemisia tabaci), which have increased to very high numbers in some African countries. Strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 44 publications
6
91
0
Order By: Relevance
“…Insects 2020, 11, 58 3 of 15 SSA1 has been separated into five sub-groups: SSA-subgroup1 (SSA1-SG1), SSA1-SG2, SSA1-SG3, SSA1-SG4, and SSA1-SG5 [10,58,[62][63][64][65].…”
mentioning
confidence: 99%
“…Insects 2020, 11, 58 3 of 15 SSA1 has been separated into five sub-groups: SSA-subgroup1 (SSA1-SG1), SSA1-SG2, SSA1-SG3, SSA1-SG4, and SSA1-SG5 [10,58,[62][63][64][65].…”
mentioning
confidence: 99%
“…Previously, Legg et al (2014) reported that the SSA1-SG1, representing the major 450 SSA1 mtCOI subgroup, was implicated in the severe CMD pandemic in East Africa. Based 451 on the subgroup classification, Wosula et al (2017) reclassified these SSA1-SG1 individuals 452 into three SNP-based groups of SSA-ECA, SSA-CA, and SSA-WA due to perceived 453 inconsistencies (e.g., SSA1-SG3, SSA1-SG5; see Ghosh et al (2015)) based solely on the 454 utilization of the short (i.e., ca. 657bp) mtCOI partial gene marker.…”
mentioning
confidence: 99%
“…Most B. tabaci collected from cassava were SSA1 and most were uninfected by any of the secondary symbionts. A later study found contrasting results (Ghosh et al , 2015). Samples of B. tabaci were collected from cassava crops across East African countries were found to be infected with a range of endosymbionts, with the predominant species being Wolbachia , Rickettsia and Arsenophonus .…”
Section: Biotic Factorsmentioning
confidence: 90%
“…Some evidence exists that endosymbiotic bacteria within B. tabaci can have both positive and negative effects on B. tabaci fitness (Kontsedalov et al , 2008; Himler et al , 2011; Ghosh et al , 2015). Portiera aleyrodidarum is a primary obligate bacterial endosymbiont of B. tabaci , and is essential to their development.…”
Section: Biotic Factorsmentioning
confidence: 99%